"What will you give us, history …?" Contemporary Debates on the Monetary System of Bulgaria in the Light of Economic History - Penchev, Pencho (Research Papers, 2025)
The paper provides a historical reconstruction of key moments in Bulgarian financial history. They are mainly concentrated in the 19th century and are related to monetary practices and traditions before the Liberation from Ottoman rule and their evolution after 1879, the political discussions and monetary dilemmas that were placed before the political elite around the birth of the Bulgarian lev and the possible impact of monetary system on the personal finances of Bulgarians approximately until the outbreak of the First Balkan War (1912). The main conclusion is that the then lawmakers found the right solution to the dilemma they faced, despite their limited knowledge and lack of experience.
Keywords: Money; Lev (currency); Bulgaria; Economic history